The Relationship of Handwashing Behaviour with Soap and Incidence of Diarrhea Among Students at Elementary School 04 Rantau Utara - Farhun Nisah; Nurhayati Nurhayati; Putra Apriadi Siregar (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Diarrhea can be defined as a condition where a person experiences an increased frequency of defecation, which results in liquid or non-solid faeces. Washing hands with soap is a fundamental and essential technique for preventing and controlling the spread of infectious diseases. Hands are one of the main routes for bacteria to enter and infect the body. Diarrhea is one of the factors causing death, so there must be prevention of diarrhea incidents. This study aimed to analyze the relationship between hand washing behavior using soap and the incidence of diarrhea.This research includes quantitative research analysis using a cross-sectional design. Research activities were conducted at State Elementary School 04 Rantau Utara from February to March 2024. The population studied in this research were all students from Elementary School 268 Negeri 04 Rantau Utara. The sampling technique used was random sampling, which resulted in a research sample of 71 people. The variables examined in this research include hand washing behavior using soap and the incidence of diarrhea.. Data was collected through questionnaires. Data analysis carried out included univariate and bivariate analysis using the Chi-Square test using SPSS version 24 software. Based on the analysis results, a p-value of 0.000 <0.05. This shows that there is a statistically significant relationship between handwashing behaviour using soap and the incidence of diarrhea. This is due to a lack of good and correct hand washing with soap, which causes diarrhoea. Many still need to understand the basic techniques for washing hands with soap properly. Having hand washing facilities and infrastructure will make it easier for children to wash their hands properly so that they can effectively break the chain of bacteria. Keywords: School Children, Diarrhea, Adequate Facilities, Hand Washing Behavior